Non–destructive damage evaluation of adaptive materials. (4th August 2014) - Blumenauer, H.; Dehne, G.; Michel, F.; Mook, G.; Pohl, J.
A damage tolerance concept is an important prerequisite for improving the performance and service life–time of adaptive structures. In conjunction with experimental and numerical tools of electromechanical damage mechanics, high–resolution NDE methods are needed to detect manufacturing defects and to monitor the damage evaluation in a self–diagnostic manner. Mechanical tests combined with non–destructive on–line investigations are used to evaluate the early stage of damaging in CFRP specimens with embedded piezoelectric patches.